Cucumber Auxin Response Factor CsARF10a Regulates Leaf Morphogenesis and Parthenocarpic Fruit Set in Tomato - Jian Xu; Pinyu Zhu; Xiefeng Yao; Yongjiao Meng; Lina Lou; Man Zhang; Guang Liu; Xingping Yang; Jinqiu Liu; Lingli Zhu; Qian Hou; Ji Li; et al. (Horticulturae, 2024)
Auxin response factors (ARFs) are pivotal transcription factors involved in many aspects of auxin-dependent developmental processes. While functions of ARFs have been extensively studied in Arabidopsis, their distinct role in cucumber remains unclear. In this study, a cucumber auxin response factor homolog, CsARF10a, was cloned and overexpressed in tomato plants. RT-qPCR analysis indicated that the expression abundance of CsARF10a was significantly decreased in cucumber leaves and female flowers, and the expression level of CsARF10a was relatively low in pollinated fruits and hormone-treated fruits compared with that in unpollinated fruits. Moreover, the overexpression of CsARF10a in tomato resulted in multiple phenotypic changes, including a wider leaf blade, delayed fruit ripening, and parthenocarpic fruit set in CsARF10a-OE lines. Taken together, our research shed light on the regulatory importance of CsARF10a in regulating various phenotype alterations and laid a solid foundation for further functional studies.